Pengaruh Program K3 Terhadap Produktivitas Karyawan PT. Sumber Permata Selaras Site Molino Morowali Utara - Adiyanti Aziza, Nunung; Widhi Kurniawan, Agung; Ilham Wardhana, Muhammad; Akbar, Abdi; Darmawan Natsir, Uhud (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
This study aims to determine the effect of occupational health and safety on the productivity of employees of PT. Source of Gems Alignment. The independent variable in this study is occupational health and safety while the dependent variable is employee productivity. The population and sample in this study are all employees of PT. Sumber Permata Selaras as many as 104 people. Data collection was carried out using a questionnaire. The data analysis technique used is multiple linear regression analysis using SPSS 29.00 for windows. The results showed that the results of the t-test analysis showed that the variable Occupational Health (X1) had a positive and significant effect on Employee Productivity (Y). The results of the t-test analysis show that the variable work safety (X2) has a positive and significant effect on employee productivity (Y). The results of the F-test show that the Occupational Health and Safety variables (X1 and X2) simultaneously have a positive and significant effect on employee productivity (Y)